Viralitas Informasi dan Independensi Penegakan Hukum: Analisis Etika Profesi terhadap Penanganan White Collar Crime di Indonesia pada Era Artificial Intelligence - Robert Sangkala; Ida Komala; Satria Ari Wibowo; Roif Roif; Ali Asari; Windi Setiawan; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid advancement of digital technology has transformed contemporary law enforcement, particularly in addressing white-collar crime involving corruption, abuse of authority, money laundering, and technology-enabled financial offenses. Simultaneously, social media and Artificial Intelligence (AI) have accelerated the dissemination of information, allowing public opinion to develop long before judicial proceedings are completed. This phenomenon challenges the independence of law enforcement officials in maintaining objectivity, professionalism, and compliance with professional ethics. This study aims to examine the influence of information virality on law enforcement independence and to formulate an ethical framework that responds to the emergence of AI and digital communication. Employing normative legal research with statutory, conceptual, case, and comparative approaches, this study finds that AI, social media, and digital misinformation intensify public pressure on investigators, prosecutors, and judges. Existing professional ethics regulations in Indonesia remain insufficient to address these technological developments comprehensively. Consequently, this study proposes the Ethical Digital Law Enforcement Framework, emphasizing independence, algorithmic accountability, information transparency, human rights protection, and digital governance as essential principles for maintaining professional law enforcement in the digital era.